2009
DOI: 10.1007/s00268-008-9899-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Evaluation of the Effectiveness of Neoadjuvant Chemoradiation Therapy in Advanced Esophageal Cancer Patients

Abstract: The clinical evaluation for CRT does not reflect the pathologic effectiveness and, even if clinical CR was achieved, viable cancer cells were still present at the primary site in the majority of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Furthermore, patients who had a CR, PR, or SD showed a longer PFS (MST: 120 days) compared to cases with PD (MST: 40 days) (p = 0.001). This indicates that patients whose tumors were well controlled tended to have longer PFS and possibly OS than patients whose tumors did not respond to the S-1 monotherapy, and these tendencies are similar to those in patients treated with chemoradiotherapy [12]. …”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, patients who had a CR, PR, or SD showed a longer PFS (MST: 120 days) compared to cases with PD (MST: 40 days) (p = 0.001). This indicates that patients whose tumors were well controlled tended to have longer PFS and possibly OS than patients whose tumors did not respond to the S-1 monotherapy, and these tendencies are similar to those in patients treated with chemoradiotherapy [12]. …”
Section: Discussionmentioning
confidence: 92%
“…Although a significant survival difference for different histopathological response was detected in survival analysis, the category standard of histopathological response would influence the trial results, for instance <5% residual tumor cells (Akutsu et al, 2009). …”
Section: Discussionmentioning
confidence: 95%
“…Chemoradiation-induced changes histologically included reactive changes such as necrosis, fibrosis, foamy histiocytes, and giant cell reactions. Due to lack of ability to demonstrate any viable and proliferative (nonnecrotic) tumor cells within the specimen, histopathologic responses were determined by dividing the viable residual tumor area by the total tumor area, which was the sum of the areas categorized under the tumor zone according to the published guideline (Becker et al, 2003;Chang et al, 2008;Akutsu et al, 2009;Tong et al, 2010). In case of a diagnostic uncertainty, pathologists reviewed the specimen on a double-headed microscope and immunohistochemical analysis for pancytokeratin was performed.…”
Section: Analysis and Assessment Of Histopathological Responsementioning
confidence: 99%
See 1 more Smart Citation
“…This strategy requires the development and availability of novel feasible biomarkers for predicting the sensitivity to chemotherapy and/or radiotherapy. We previously reported that good pathological effectiveness of CRT in the primary tumor was closely associated with good outcome [22] . However, at present, the rate of response to neoadjuvant CRT is unsatisfactory [23] .…”
Section: Discussionmentioning
confidence: 99%